Computational drug repositioning for rare diseases in the era of precision medicine. Issue 2 (February 2018) - Delavan, Brian; Roberts, Ruth; Huang, Ruili; Bao, Wenjun; Tong, Weida; Liu, Zhichao
Highlights: Next-generation sequencing technology accelerates rare disease research. Accumulated genomics information aids orphan drug development. Novel drug repositioning approaches for rare diseases facilitate precision medicine. Efforts from different stakeholders boost rare disease treatment development. Abstract : There are tremendous unmet needs in drug development for rare diseases. Computational drug repositioning is a promising approach and has been successfully applied to the development of treatments for diseases. However, how to utilize this knowledge and effectively conduct and implement computational drug repositioning approaches for rare disease therapies is still an open issue. Here, we focus on the means of utilizing accumulated genomic data for accelerating and facilitating drug repositioning for rare diseases. First, we summarize the current genome landscape of rare diseases. Second, we propose several promising bioinformatics approaches and pipelines for computational drug repositioning for rare diseases. Finally, we discuss recent regulatory incentives and other enablers in rare disease drug development and outline the remaining challenges.